Diagnostic accuracy, clinical utility and influence on decision‐making of a methylation urine biomarker test in the surveillance of non‐muscle‐invasive bladder cancer. (5th February 2019) - D'Andrea, David; Soria, Francesco; Zehetmayer, Sonja; Gust, Kilian M.; Korn, Stephan; Witjes, J. Alfred; Shariat, Shahrokh F.
Abstract : Objectives: To investigate prospectively the clinical utility and influence on decision‐making of Bladder EpiCheck™, a non‐invasive urine test, in the surveillance of non‐muscle‐invasive bladder cancer (NMIBC). Materials and Methods: Urine samples from 440 patients undergoing surveillance for NMIBC were prospectively collected at five centres and evaluated using the Bladder EpiCheck test (NCT02647112). A multivariable nomogram and decision‐curve analysis (DCA) were used to evaluate the impact of Bladder EpiCheck on decision‐making when used in routine clinical practice. The test was designed to exclude recurrent disease. Results: Data from 357 patients were available for analysis. The test had a specificity of 88% (95% confidence interval [CI] 84–91), a negative predictive value (NPV) of 94.4% (95% CI 91–97) for the detection of any cancer and an NPV of 99.3% for the detection of high‐grade cancer. In multivariable analysis, positive Bladder EpiCheck results were independently associated with any and high‐grade disease recurrence (odds ratio [OR] 18.1, 95% CI 8.7–40.2; P < 0.001 and OR 78.3, 95% CI 19.2–547; P < 0.001). The addition of Bladder EpiCheck to standard variables improved its predictive ability for any and high‐grade disease recurrence by a difference of 16% and 22%, respectively (area under the curve 85.9% and 96.1% for any and high‐grade cancer, respectively). DCA showed an improvement in the net benefit relative to cystoscopy over a large threshold of probability, resulting in a significant reduction in unnecessary investigations. These results were similar in subgroups assessing the impact of specific clinical features. Conclusions: Bladder EpiCheck is a robust high‐performing diagnostic test in patients with NMIBC undergoing surveillance that can potentially reduce the number of unnecessary investigations.